2014
DOI: 10.1097/fbp.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam results in increased and decreased alcohol drinking with different access procedures in C57BL/6J mice

Abstract: The antiepileptic, levetiracetam (LEV), has been investigated for the treatment of alcohol abuse. However, little is known about how LEV alters the behavioral effects of alcohol in laboratory animals. The acute effects of LEV on alcohol drinking by male C57BL/6J mice were investigated using two different drinking procedures, limited access (drinking-in-the-dark, or DID) and intermittent access (IA) drinking. In the first experiment (DID), mice had access to a single bottle containing alcohol or sucrose for fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Therefore, this enhanced glutamate response appears to reflect ethanol experience-dependent neuroadaptation. Interestingly, the antiepileptic drug levetiracetam, which potently inhibits vesicular release of glutamate (Meehan et al, 2011; Meehan et al, 2012), has been shown to increase ethanol intake in male B6 mice during a 4-hr DID procedure (Fish et al, 2014). In conjunction with the microdialysis data described above, this observation may reflect a compensatory increase in ethanol intake to oppose the drug-induced reduction in glutamatergic tone.…”
Section: Mechanisms Of Binge-like Alcohol Consumptionmentioning
confidence: 99%
“…Therefore, this enhanced glutamate response appears to reflect ethanol experience-dependent neuroadaptation. Interestingly, the antiepileptic drug levetiracetam, which potently inhibits vesicular release of glutamate (Meehan et al, 2011; Meehan et al, 2012), has been shown to increase ethanol intake in male B6 mice during a 4-hr DID procedure (Fish et al, 2014). In conjunction with the microdialysis data described above, this observation may reflect a compensatory increase in ethanol intake to oppose the drug-induced reduction in glutamatergic tone.…”
Section: Mechanisms Of Binge-like Alcohol Consumptionmentioning
confidence: 99%